2021
DOI: 10.1080/14735903.2021.1916254
|View full text |Cite
|
Sign up to set email alerts
|

Two enabling factors for farmer-driven pollinator protection in low- and middle-income countries

Abstract: Reward-based wildflower strips are the most common approach for pollinator protection in high-income countries. Low-and middle-income countries cannot afford this practice. A promising pilot study in Uzbekistan introduced an alternative approach, Farming with Alternative Pollinators, focusing on farmers as target group, marketable habitat enhancement plants and a method-inherent incentive: higher income per surface achieved already in the first year. We hypothesized that higher income would be a replicable ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…The impact of reducing 25% of the surface of faba bean and increasing the diversity of floral resources in favor of pollinators was visible in pollinator abundance and species richness in the whole fields. Similar to two pilot projects (Christmann et al 2017(Christmann et al , 2021, our experiment showed FAP-induced benefits for pollinator conservation. This approach should be assessed in other countries and different insect pollinated crops, as using MHEP might be more acceptable for farmers than e.g.…”
Section: Pollinator Species Overlap In Fap Fieldssupporting
confidence: 64%
See 2 more Smart Citations
“…The impact of reducing 25% of the surface of faba bean and increasing the diversity of floral resources in favor of pollinators was visible in pollinator abundance and species richness in the whole fields. Similar to two pilot projects (Christmann et al 2017(Christmann et al , 2021, our experiment showed FAP-induced benefits for pollinator conservation. This approach should be assessed in other countries and different insect pollinated crops, as using MHEP might be more acceptable for farmers than e.g.…”
Section: Pollinator Species Overlap In Fap Fieldssupporting
confidence: 64%
“…"Farming with Alternative Pollinators" (FAP) (Christmann and Aw-Hassan 2012; Christmann et al 2017Christmann et al , 2021Christmann 2019b) is a new approach aiming to increase farm income as an incentive for farmers to engage in pollinator protection. Alternative pollinators refer to wild pollinators that farmers currently do not value for their wide contribution in agricultural production (Christmann et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are not necessarily fallow areas, as many ground‐nesting pollinators prefer arable land or pastures (Cope et al, 2019 ; Skidmore et al, 2019 ). Within the land‐sharing approach Farming with Alternative Pollinators (FAP; Christmann, Aw‐Hassan, et al, 2021 ; Christmann, Bencharki, et al, 2021 ; Christmann et al, 2017 ) this land can be used for (perennial) marketable habitat enhancement plants (MHEP), fruit trees, berries, cactus, alfalfa, mint, lavender, etc., planted as corridors or hedgerows. The insect diversity attracted by MHEP enhances the productivity of pollinator‐dependent main crops (Christmann, Aw‐Hassan, et al, 2021 ; Christmann, Bencharki, et al, 2021 ; Christmann et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing the effect of reduction of fertilizer input, irrigation, and pollination, found that a reduction of insect pollination has a stronger effect on crop yield than other agricultural inputs (Fijen et al, 2020). Furthermore, insect pollination enhances the yield and the quality of many crops at both the local and global scale, such as for faba bean (Aouarsadli et al, 2008;Cunningham and Le Feuvre, 2013), strawberries (Abrol et al, 2019;MacInnis and Forrest, 2019), apple (Garratt et al, 2014a;Hünicken et al, 2021), eggplant (Jayasinghe et al, 2017), cucumber (Christmann et al, 2017(Christmann et al, , 2022, and tomato (Bashir et al, 2018;Toni et al, 2020). Moreover, many countries are becoming increasingly dependent on pollinators because production has shifted to more pollinator-dependent crops (Aizen et al, 2008;Potts et al, 2016).…”
Section: Introductionmentioning
confidence: 99%